Plasma retinol-binding protein-4 and tumor necrosis factor-α are reduced in postmenopausal women after combination of different intensities of circuit resistance training and Zataria supplementation - Tayebi, Seyed Morteza (Sport Sci Health, 2019)
PURPOSE: Zataria is a plant with anti-inflammatory properties, which has been used for the treatment of many diseases. This study investigated the effect of different intensities of circuit resistance training and Zataria supplementation on plasma retinol-binding protein-4 (RBP-4) and tumor necrosis factor-α (TNF-α) in postmenopausal women. METHODS: Seventy-two postmenopausal women were divided on randomized order into six groups: Control (McGinley and Bishop in J Appl Physiol 121(6):1290–1305, 2016), Training 35% (T35%), Training 55% (T55%), Zataria (Özgünen et al. in Scand J Med Sci Sports 20:140–147, 2010), Zataria/Training 35% (ZT35%), and Zataria/Training 55% (ZT55%). Resist-ance training program included 12 exercise stations (each: 30 s, intensity: 35% and 55% of 1-RM) for 8 weeks (3 sessions/week). Daily (500 mg) Zataria was used after breakfast by participants in ZG, ZT35%, and ZT55% groups. Blood samples were taken 48 h before and after the first and last sessions of training. RESULTS: After the training period the percentage of body fat decreased significantly (P < 0.001) in all trained groups, whereas muscle mass increased significantly (P < 0.01) only in T55% and ZT55% groups. A significant decrease was observed for RBP-4 values (P < 0.05) after training in all groups except for ZG and CG. Also, RBP-4 was significantly lower (P < 0.05) in all groups as compared to CG at the post-test except for ZG. Moreover, significantly lower values (P < 0.05) were found in T55%, ZT35%, and ZT55% as compared to ZG in post-intervention. TNF-α values decreased significantly (P < 0.05) at the post-test as compared to pre-intervention in ZT35% and ZT55%. Also, TNF-α was significantly lower (P < 0.05) in ZT55% compared to CG and T35% in post-test CONCLUSIONS: The results demonstrate clearly that in postmenopausal women, circuit resistance training both at low and moderate intensities cause a greater reduction in RBP-4 and TNF-α when Zataria is supplemented in the diet during training.